Vanadium Supplementation vis-a-vis Growth and Nutrient Utilization in Karan Fries Calves - Kumar, Rajesh; Kewalramani, Neelam; Pal, Ravi Prakash; Mani, Veena (Indian Journal of Animal Nutrition, 2017)
In order to study the influence of vanadium on growth and nutrient utilization, twenty four Karan fries male calves of 3-6 months of age were divided into 4 groups of 6 animals each. All the animals were fed rations comprising of concentrate mixture, green fodder and wheat straw to meet their nutrient requirement (ICAR, 2013). However, vanadium was also given to animals in treatment groups T1, T2 and T3 @ 3, 6 and 9 ppm, respectively for a period of 165 days. Vanadium supplementation did not have any significant effect on DM, CP and TDN intake and digestibility of CP, EE, NDF and ADF. Up to level of 9 ppm, no beneficial or adverse effect on the average body weight and daily gain of Karan fries calves was observed. It was concluded that supplementation of vanadium up to a level of 9 ppm did not influence the growth rate and nutrient digestibility in Karan fries male calves.